PENGARUH SARANA PRASARANA TERHADAP KINERJA GURU - Fudin, Armansyah (Universitas Muhammadiyah Surakarta, 2020)
This study aims to describe the effect of infrastructure on the performance teachers in SMA Negeri 1 Matan Hilir Utara Ketapang district. The approach in this research uses quantitative. This type of research is a correlation. data collection using a questionnaire. The population in this study were all teachers, administrative staff and students, and principals in SMA Negeri 1 MHU Ketapang district. The sample in this study amounted to 30 people. The research findings show that the comparison of the value of t_count t_table (3.323 2.048), which shows the positive influence of school infrastructure on the performance of teachers in SMA Negeri 1 Matan Hilir Utara Ketapang district.Keywords: Means of Prasana, Teacher Performance